Amino Acids and their Derivatives in Pathogenesis and Treatment of Liver Diseases - I.I. Nefyodov; A.J. Karakosh; M.A. Alufaini; P.A. Karavay; N.L. Karavay (Journal of Hematology and Oncology Research, 2019)
A mini-review of literature data on the mechanisms of formation of the stock of free amino acids and their derivatives in liver pathology and methods for correcting metabolic imbalance
Keywords: amino acids